Petri-net based modelling approach for ALFRED reactor operation and control system design. (March 2016) - Ponciroli, Roberto; Cammi, Antonio; Lorenzi, Stefano; Luzzi, Lelio
Abstract: In this work, the Petri-net modelling approach applied to the control system design of the Advanced Lead Fast Reactor European Demonstrator (ALFRED) is presented, paying particular attention to the startup procedure. The reactor startup is the operational transient in which all the systems of the plant are brought from the cold shutdown condition to the full power mode, close to load-frequency control. In this phase, the several control actions to be taken need to be properly coordinated. To this end, the operational sequence which constitutes the reactor startup procedure has been described by adopting the Petri-nets approach, i.e., a useful formalism for the modelling and the analysis of Discrete Event Systems. Thanks to this quantitative representation, it is possible to easily derive the corresponding control scheme. In addition, the Petri-nets approach has been also exploited for the two-level control system architecture, namely a master system coordinates the operation of the plant by sending suitable signals to the slave system, in which feedback controllers are implemented. As a major outcome of this work, the procedure for the reactor startup and the transition to the full power mode has been simulated in order to assess the control system performance. Highlights: Design of a suitable operational procedure for the reactor startup of a Gen-IV Lead-cooled Fast Reactor. Realization of a synchronized Petri-net representing the desired evolution of the ALFRED reactor startup. Design of the preliminary configuration of the two-level control system architecture. Simulation of the reactor startup procedure by adopting an object-oriented simulator.